Communication skills - Leena Sen (Prentice Hall of India Private Limited, 2008)
Today, the need for communication skills has become more important than ever before. Communication plays a vital role - be it the preparation one has to do to face an interview or deal with diverse business deals, or interacting with colleagues, superiors, and others. The Second Edition of this text, based on the feedback received from the readers, continues to highlight the vital skills one needs for effectively communicating in diverse situations.Divided into five parts, the text shows the power of three V's of communication - the verbal, the visual and the vocal, examining at the same time the role of formal and informal communication methods, and stressing the significance of grapevine in organizations. It also demonstrates how important listening is, and the basic skill-sets needed by a manager for business dealings. Further, the text gives the nuances of verbal communication and the factors necessary for preparing a presentation besides giving a comprehensive view of non-verbal communication. It highlights the role of written communication, the importance of business writing, the formats of business letters, memos, and report writing, and how flawed thinking impedes written communication. The text concludes by emphasizing the crucial role played by corporate communication in enhancing an organization's image.It covers new concepts such as Fog Index/Readability Index, Business Terms, Acronyms, Abbreviations, e-mail Etiquette, Virtual Team Skills, and Social Skills. It includes many exercises and other inputs.Written in a clear and straightforward style and in a student-friendly fashion, this concise and compact text is intended both for students of management and for young executives and managers.